AN ANALYSIS OF SPECIALIZED VOCABULARY FREQUENCY, LEXICAL DENSITY, AND MULTIMODALITY IN STUDENTS’ WRITING IN AN EMI CLASS: A CORPUS-BASED STUDY - Sanni, Fitri Aulia; Wirza, Yanty (International Journal of Education, 2025)
Corpus analysis plays pivotal role in investigating language use within EMI contexts. However, there is still a lack of research on identifying specialized vocabulary with its lexical density along with the multimodal analysis in the science education context. This research aims to identify frequently used specialized vocabulary, measure lexical density, and investigate multimodality in the students’ writing. Quantitative and qualitative methods using AntConc and Compleat Lexical Tutor and Kress and Leeweun multimodal analysis framework were employed. The data, totaling 12.587 words, were collected from mindmap assignments, submitted by 62 students at the International Program in Science Education, specifically in the Biotechnology subject, over a span of four consecutive years. The findings showed 20 specialized vocabularies in Biotechnology based on the frequency. The lexical density of the data ranges from 61% to 97%, or by average 78%, indicating that the majority of these words are disciplinary-related content words. This study also revealed the interconnection of the visual and verbal elements in the meaning-making of the disciplinary concepts. This study confirms that the specialized vocabulary, lexical density, and multimodality are interrelated components of communication in specialized domains, which should be considered for pedagogical purposes.